Metabolic characteristics of the various incision margins for breast cancer conservation surgery - Wang, Fang; Gu, Zongze; Zhao, Xunan; Chen, Zhuo; Zhang, Zhe; Sun, Shihao; Han, Mingli (Frontiers in Oncology, 2023)
BACKGROUND: In recent years, breast cancer (BC) has become the most prevalent malignancy in women. There are many alternative treatments for BC, and for aesthetic and postoperative quality of life concerns, breast-conserving surgery and corresponding adjuvant therapy have become the predominant treatment for early invasive BC. Currently, the main method of assessing the margins of breast-conserving surgery is intraoperative pathological diagnosis. However, surgical margins have been controversial and metabolomics may be a novel approach to evaluate surgical margins. METHODS: We collected 10 cases of breast cancer and its surrounding tissues and divided them into cancerous tissue, 1 mm, 2 mm, 3 mm, 5 mm and 10 mm cutting edge tissues, with a total of 60 samples. The samples were analyzed by mass spectrometry on an ultra performance liquid chromatography-quadrupole/Orbitrap high resolution mass spectrometry platform. The data were then statistically analyzed to detect metabolic changes in the different cutting edges and to identify possible surgical cutting edges with statistical significance. Metabolic abnormal pathways were analyzed by Kyoto Encyclopedia of Genes and Genomes (KEGG), which in turn identified potential markers. RESULTS: Statistical analysis of the data indicated that there were substantial differences between the 1mm margin tissue and the cancer tissue, while there were no statistically significant differences between the 1mm and the other margin tissues. Six differential metabolites in the 1mm cut edge tissue were statistically significantly different from the cancer tissue and not significantly different from the 2mm cut edge tissue. The six metabolites were pyruvate, N-acetyl-L-aspartate, glutamic acid, γ-aminobutyric acid, fumaric acid, and citric acid. Metabolic pathways such as amino acid metabolism and amino t-RNA synthesis were significantly distinct from cancer tissues by KEGG analysis. CONCLUSION: There is a significant difference between the 1mm margin tissue and the cancerous tissue. From a metabolomic point of view, the 1mm negative margin is sufficient for surgery, and the six metabolites which are Pyruvic acid, N-Acetyl-L-aspartic acid, Glutamic acid, gamma-Aminobutyric acid, Fumaric acid and Citric acid we identified as abnormal metabolites may serve as biomarkers for a negative margin and help surgeons to select a more appropriate surgical margin.